Rhetorics of Belonging Nation, Narration and Israel/Palestine - Bernard, Anna (Liverpool University Press, 2018)
Describes the formation and operation of a category of Palestinian and Israeli 'world literature' whose authors actively respond to the expectation that their work will 'narrate' the nation, invigorating critical debates about the political and artistic value of national narration as a literary practice. The crisis in Israel/Palestine has long been the world's most visible military conflict. Yet the region's cultural and intellectual life remains all but unknown to most foreign observers, which means that literary texts that make it into circulation abroad tend to be received as historical documents rather than aesthetic artefacts. Rhetorics of Belonging examines the diverse ways in which Palestinian and Israeli world writers have responded to the expectation that they will 'narrate' the nation, invigorating critical debates about the political and artistic value of national narration as a reading and writing practice.